Ultrasonographic method as confirmatory test for feeding tube placement in mechanically ventilated patients - Saw, Yee Horng; Ramly, Nur Fariza; Mohammad Aidid, Edre; Ab Rahman, Najibah Syakirah; Soo, Ki Yang (Faculty of Medicine Universiti Kebangsaan Malaysia, 2021)
Objective: Nasogastric feeding tube placement is common procedure in intensive care units (ICU). Although the incidence of misplacement is rare but it is dreadful for the patients. This study objective is to estimate the accuracy of ultrasonography method in confirming feeding tube placement. Methods: 80 ICU patients were included, feeding tube placement will be assessed by ultrasonography through 3 points. First point, visualization of feeding tube in cervical esophagus at left anterolateral of neck. Second point, visualization of feeding tube at sub-xiphoid or left upper abdominal quadrant. Third point, injection of only air and look for dynamic fogging using color Doppler flow. Presence of feeding tube in any sonographic assessment points consider in-situ. Final confirmation will be assessed using chest X-ray (CXR). Time for each method will be recorded. Results: Total 78 patient’s feeding tube placement were in-situ, confirmed by chest X-ray. Sensitivity, specificity of cervical esophagus assessment was 68%/0%, subxiphoid 31%/100%, and dynamic fogging 97%/100% respectively. Combination of cervical esophagus assessment with sub-xiphoid or dynamic fogging does improve sensitivity up to 100%, but adversely affect specificity down to 0%. Combination of Sub-xiphoid and dynamic fogging yield 100% sensitivity and 100% specificity. Accuracy of each ultrasound method were not affected by gender or body mass index (BMI). Entire sonographic procedure took 3 minutes (+ 0.8) while chest X-Ray took 61 minutes (+ 87). Conclusions: Sub-xiphoid and dynamic fogging sonography assessment were valuable in confirming placement of feeding tube in-situ, however cervical esophagus assessment can be helpful in identify feeding tube pass through esophagus but not final in-situ placement. Sonography methods carry the potential to be reliable alternative method in feeding tube placement, however larger studies are required to strengthen evidence.